Bringing emotion and personal narrative into medical social science - Ellis, Carolyn; Bochner, Arthur P. (Health (London, England : 1997), 1999)
A comment on Rose Weitz's "Watching Brian Die: The Rhetoric and Reality of Informed Consent" (1999) argues that, in adhering to clinical observation as a methodology, medical social science marginalizes the emotional & bodily aspects of medical crises. The influence of this methodology on Weitz's article is discussed. It is suggested that medical social science should empathize with, as well as observe, its subjects. 32 References. J. Ferrari